Conceptualizing Deep Learning Approach in Primary Education: Integrating Mindful, Meaningful, and Joyful - Nafi'ah, Jamilatun; Faruq, Dukan Jauhari (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
According to PISA 2022, Indonesian students scored 359 in reading, 366 in mathematics, and 19 in creative thinking, all well below the OECD average of 476, 472, and 33, respectively. The era of instant information from artificial intelligence (AI) and social media has also contributed to the decline in students' cognitive quality. Therefore, mindful, meaningful, and joyful deep Learning has been implemented as a learning approach in Indonesia. This study aims to examine how the concept and application of mindful, meaningful, and joyful deep Learning as a learning approach is implemented in primary education in Indonesia. The study was conducted systematically by analysing five scientific articles published between 2022 and 2025. Literature searches were conducted through Google Scholar, Research Gate, and Sinta, with the selection process following the PRISMA flow. The research findings indicate that deep Learning effectively promotes the development of critical, creative, reflective, and emotional thinking patterns and student engagement when applied contextually by aligning with students' life experiences. However, challenges such as teacher readiness and limitations in infrastructure and learning technology remain obstacles to implementation. These findings emphasise the importance of large-scale empirical studies on mindful, meaningful, and joyful deep learning approaches in the context of primary education as a reference for educational institutions in implementing them.